An Analysis of English Learning Content on YouTube for EFL Learners: A Focus on Speaking Skills Study at MTs N Kota Sorong - Putri Lestari (Program Studi Pendidikan Bahasa Indonesia, Institut Pendidikan Nusantara Global, 2026)
Digital tech has exploded lately, completely changing how people learn English as a foreign language with YouTube leading the charge as a top player. This article takes a close look at English content on YouTube, zeroing in on how it helps EFL students build speaking skills, spotlighting kids from MTs N Kota Sorong as a key example within Indonesia's wider EFL scene. Pulling from past studies and in-depth reviews, it breaks down YouTube's boost to pronunciation work, chat skills, fluency, and overall confidence. The results make it clear: the platform delivers genuine spoken English, engaging multi-format lessons, and chances for self-guided practice, turning it into a solid sidekick for speaking growth. That being said, issues like uneven video quality, lack of direct feedback, and the need for student discipline still pop up. Overall, the paper spells out practical teaching takeaways for using YouTube to level up speaking abilities in EFL settings.